The Effectiveness of Mugwort Leaf Extract and Gotu Kola Leaf Extract against Acne Bacterial Activity - Diah Puspita Sari; Shintya Yuniar; Siti Awalia Nur Fadillah; Afifi Mutiarani; Diah Kusumawaty (ASEAN Journal of Science and Engineering, 2022)
Acne is a problem among teenagers generally caused by bacterial infections such as Propionibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis. Mugwort (Artemisia vulgaris L.) and Gotu Kola (Centella asiatica L.) extracts have antibacterial activity formulated in anti-acne gel preparations. The purpose of this study was to test and obtain a gel formula of mugwort leaf extract and gotu kola leaf extract which effectively kills and controls the growth of acne-causing bacteria. The methods used in this study include simplicity making, leaf extraction, making anti-acne gel preparations, testing pH, homogeneity, inhibition, and data analysis. The extract obtained by maceration was made in three concentrations, namely 2.50; 5.00; and 10.00%. The results showed that the pH value of the gel preparations obtained was in the range of 8.08-9.96. Mugwort leaf extract, gotu kola leaf, and mugwort-gotu kola have a distinctive smells with a thick texture at a concentration of 2.50% and a liquid texture at a concentration of 10.00%. Inhibition tests showed that the mugwort extract sample had a value of 16-18 mm, while the gotu kola extract and mugwort-gotu kola had a value of 14 mm. Mugwort leaf extract is able to inhibit the growth of acne-causing bacteria. This success was obtained because the extracts of mugwort and gotu kola leaves contain flavonoids that can inhibit the growth of bacteria that cause acne. Mugwort leaf extract gel with a concentration of 2.50 and 5.00% had the largest zone of inhibition in inhibiting P. acnes bacteria compared to other concentrations.